Pilot plant production of craft fruit beer using Ohmic‐treated fruit puree. Issue 2 (1st November 2019) - Fanari, Mauro; Forteschi, Mauro; Sanna, Manuela; Piu, Piero Pasqualino; Porcu, Maria Cristina; D'hallewin, Guy; Secchi, Nicola; Zinellu, Manuel; Pretti, Luca
Abstract: Fruit beers are a special type of beers made with fruit addition in the production process. They are becoming popular especially in the field of craft breweries. Their production can be influenced by the seasonality of fruit harvest and by the risk of contamination due to the presence of microorganisms on the fruit skin. The purpose of the present study was to verify the use of sterile Ohmic‐treated fruit puree, with good sensorial characteristics and a longer shelf life, for fruit craft beer production. Fresh and sterile cherry and plum puree was added in fermentation phase, and the effects on standard quality attributes, chemical composition, and sensory profile were compared. The differences observed in chemical, physical, and sensorial analyses did not affect the acceptability of the beers. Practical applications: This study shows that Ohmic‐treated fruit puree is a good option to deseasonalize fruit beer production, keeping a high qualitative sensory profile avoiding spoilage risk.